Sparse‐Flowering Orchardgrass is Stable Across Temperate North America. Issue 5 (1st September 2013) - Casler, M. D.; Papadopolous, Y. A.; Bittman, S.; Mathison, R. D.; Min, D. H.; Robins, J. G.; Cherney, J. H.; Acharya, S. N.; Belesky, D. P.; Bowley, S. R.; Coulman, B. E.; Drapeau, R.; et al.
ABSTRACT: Orchardgrass ( Dactylis glomerata L.) is a major component of many pastures in temperate North America. Early and profuse flowering in pastures is problematic due to livestock refusal to consume flowering stems. The objective of this research was to determine the stability and agronomic impact of recently developed sparse‐flowering orchardgrass populations across temperate North America. Six cultivars, three sparse flowering and three normal flowering, were grown at 21 locations in temperate North America and evaluated for panicle density, heading date, and forage yield. Sparse‐flowering cultivars had 57% fewer panicles than normal‐flowering cultivars, but this effect was highly dependent on mean winter temperature, with normal‐flowering cultivars showing twice as much temperature sensitivity compared to sparse‐flowering cultivars. Forage yield of sparse‐flowering cultivars was reduced by approximately 24 to 32% for first harvest and 2 to 9% for regrowth harvests compared to normal‐flowering cultivars and this reduction in forage yield was independent of mean winter temperature. The forage yield reduction associated with sparse flowering is most likely due to a combination of physiological load (loss of stems) and opportunity cost (lack of selection pressure for yield), suggesting an opportunity to improve forage yield potential of this sparse‐flowering germplasm pool.